CATALOG DEVELOPMENT OF BETTA FISH TYPES USING PHOTO AND AUGMENTED REALITY AS INFORMATION AND PROMOTION MEDIA FOR INDONESIAN BETTA FISH - Syaeful Anas Aklani; Alex Setiawan (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
In today's modern era, there are many ways to promote a product to the wider community, one of which is by using catalogs. Catalogs are known as effective promotional media as they present information and product images in a visually appealing manner. In this study, we will develop a catalog with an augmented reality feature that will appear when the catalog pages are scanned using certain applications. This catalog was created to introduce a variety of popular betta fish in Indonesia to the public. In this development, MDLC (Multimedia Development Life Cycle) will be used since it considered the most suitable method for catalog development